Application of activated carbon/ TiO2 composite for ammonia degradation from leaching process in methyl iso cyanate production - Syaputra, Muhammad Rifki; Hamdi, Hilal; Permana, Sidik Maulana; Arlofa, Nina; Elysabeth, Tiur (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
The wastewater in the washing process in Methyl Iso Cyanate production line contains ammonia which causes air pollution. Therefore, the ammonia waste processing system is needed that can degrade ammonia so that its concentration decreases and reduces the pollution. Photocatalytic degradation of ammonia is an attractive technology because of its easy operation, high efficiency, low cost, and low secondary pollutants. The photocatalytic process produces hydroxyl groups from the decomposition of water which can oxidize ammonia into nitrate and nitrogen gas. This research aims to process ammonia waste by combining adsorption and photocatalysis processes to obtain better performance in degrading ammonia. The research began with the preparation of activated carbon as an adsorbent and the synthesis of activated carbon-TiO2 composite material. Activated carbon is heated at 500º C for 6 hours for the activation process. Composite material synthesis is carried out using the slurry method. Activated carbon performance testing was carried out at weight variations of 10, 20 and 30 gram. Measurement of ammonia concentration was carried out using the spectrophotometry method. Optimum results were obtained at an activated carbon weight of 30 gram with a reduction in ammonia concentration of 1.01%. TiO2 as much as 5% of the weight of activated carbon (30 gram) is dissolved in ethanol and activated carbon is added to obtain a composite material. In the composite material performance test, a maximum reduction in ammonia concentration of 45% was obtained using the ultrasonic stirring method.